Turkish EFL teachers’ attitudes towards online instruction throughout the Covid-19 outbreak - Civelek, Mustafa; Toplu, Işılay; Uzun, Levent (Universitas Ahmad Dahlan, 2021)
The purpose of the present study is to shed light on the attitudes of Turkish EFL teachers towards online instruction (OI), the impact of training on their attitudes, the obstacles they encounter, and the strategies to deliver OI more successfully throughout the Covid-19 outbreak. The participants were 70 EFL teachers (52 female, 18 male). The data was collected through a questionnaire and semi-structured interviews. The data were analyzed by using SPSS 26. Descriptive statistics of each item was calculated and an independent sample t-test was conducted to answer the research questions. For the analysis of the interview data, the responses of the participants were transcribed and the recurring themes were identified. The results revealed that the attitudes of Turkish EFL teachers, who experienced online instruction during the Covid-19 outbreak, are not as positive as expected regarding some of the results of the related research in the literature. The interview findings revealed that EFL teachers do not feel capable of delivering online instruction effectively since they do not have adequate knowledge and necessary skills to do that. In view of the findings, it’s suggested that online instruction methodology should be integrated into teacher training programs and teachers should receive an in-service training about the related subject.